1993
DOI: 10.1111/j.1365-2842.1993.tb01607.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of intermediary resins when bonding glass polyalkenoate (ionomer) cement to composite resin

Abstract: This study was designed to examine the effects of three different types of glass polyalkenoate lining cement combined with three different types of bonding resin and varying surface treatments on the seal between the lining cement and the composite resin as used in the so called 'laminate' technique. The seal was assessed using a radioisotope and autoradiographic technique. Results showed that all the cements behaved in a manner specific to them. The seal of all systems examined could be improved, or at least,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…[19] However, application of resin bonding agents promotes the adhesion of the resin composite to both conventional GIC and RMGIC. [20] Moreover, hydroxyethylmethacrylate (HEMA) incorporated into the glass ionomer cement, forms a chemical bond with the resin of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…[19] However, application of resin bonding agents promotes the adhesion of the resin composite to both conventional GIC and RMGIC. [20] Moreover, hydroxyethylmethacrylate (HEMA) incorporated into the glass ionomer cement, forms a chemical bond with the resin of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…[1621] In the current study, both self-etch adhesive systems had higher SBS than the total-etch adhesive. This finding is consistent with the results obtained by Arora et al [9] and Kasraie et al [16] Similarly, Kandaswamy et al [2] concluded that mild self-etch adhesive had higher bond strength than the strong self-etch or total etch adhesive when they were applied on the unset GI cement.…”
Section: Discussionmentioning
confidence: 76%
“…The use of resin adhesive agents promotes RMGIC adherence to resin composites. 8 Furthermore, hydroxyethylmethacrylate integrated into the resin composite, builds a chemical adhesion with the RMGIC.…”
Section: Introductionmentioning
confidence: 99%